Hydrophobic effect for anionic dye - cationic surfactant interaction in aqueous and mixed solvent. Issue 8 (3rd August 2019) - Ramadan, Mohamad Sh.; El-Mallah, Nabila M.; Nabil, Gehan M.; Abd-Elmenem, Sherif M.
Abstract: The interaction between anionic dyes [Reactive Orange 122 (R.O 122), Reactive Blue 19 (R.B 19), Reactive Violet 5 (R.V 5) and Acid Green 20 (A.G 20)] with cationic surfactant cetyltrimethylammoniun bromide (CTAB) has been investigated by spectrophotometry and conductance technique. The used dyes are characterized by tautomeric behavior which affects the mechanism of the interaction. Various parameters such as dye structure, surfactant composition, solvent composition, temperature and pH of the medium were studied. The spectral data were applied for calculating the binding constant between dye and surfactant (Kb ), fraction of micellization (ƒmic ), and standard free energy change of binding (ΔG°b ) in 0, 10, 20 and 30 v/v % acetonitile (AN). Conductance technique was constructed to estimate the ion pairing constant (Ka ) at different temperatures and v/v % AN. Thermodynamic parameters (ΔG°, ΔH° and ΔS°) for ion pair formation were evaluated. The role of hydrophobic and electrostatic effect on dye-surfactant interaction was discussed. Graphical Abstract: The interaction between anionic dyes [Reactive Orange 122 (R.O 122), Reactive Blue 19 (R.B 19), Reactive Violet 5 (R.V 5) and Acid Green 20 (A.G 20)] with cationic surfactant cetyltrimethylammoniun bromide (CTAB) has been investigated by spectrophotometry and conductance technique. Visible spectra(a) and specific conductance (b) of R.O122-CTAB system in 10% v AN at 25 °C (dye concentration 1x10 −4 mol L −1 ) CMC of R.O122/CTAB =1.2x10 −4 molL −1 .Key words: dye structure, solvent composition, spectral character, hydrophobic effect, conductance.